1996
DOI: 10.4269/ajtmh.1996.55.370
|View full text |Cite
|
Sign up to set email alerts
|

The Spleen in Murine Plasmodium Chabaudi Adami Malaria: Stromal Cells, T Lymphocytes, and Hematopoiesis

Abstract: Morphologic and functional changes in the spleen of BALB/cByJ mice in the course of Plasmodium chabaudi adami malaria were assessed by light and electron microscopy, augmented by probes of polystyrene spheres and autoradiography of injected 3H-uridine-labeled T lymphocytes. The initial phase of the disease (precrisis) was characterized by increasing parasitemia accompanied by a marked increase in spleen size and by anemia. Erythropoiesis predominated, but there was also plasmacytopoiesis and monocyte-macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
5

Year Published

1998
1998
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 0 publications
2
26
1
5
Order By: Relevance
“…1B and C). This state of the spleen, referred to as "closed" below, has been reported to occur transiently in nonlethal infections with P. yoelii 17XNL (32) and P. chabaudi adami (2). However, the data in Fig.…”
Section: Resultscontrasting
confidence: 51%
See 1 more Smart Citation
“…1B and C). This state of the spleen, referred to as "closed" below, has been reported to occur transiently in nonlethal infections with P. yoelii 17XNL (32) and P. chabaudi adami (2). However, the data in Fig.…”
Section: Resultscontrasting
confidence: 51%
“…When the precrisis phase culminates in peak parasitemia, reopening of the filtration beds is associated with an increased trapping activity that is presumably due to malaria-induced splenomegaly (32), and this has been correlated with rapidly decreasing parasitemia in the following crisis phase. In another avirulent malaria model, Plasmodium chabaudi adami infection of BALB/c mice, such transient changes in trapping were further substantiated using fluorescent polystyrol particles (2). By contrast, Yadava et al (36) did not find, with exactly the same parasite/host combination, any evidence for reduced splenic trapping of either Salmonella enterica serovar Typhimurium in the MZ or pRBC in the red pulp, and they concluded that the pRBC avoid a fully functional MZ.…”
mentioning
confidence: 96%
“…For example, we know that immunized mice depleted of CD4 + T cells offer more resistance to infection than naive mice, suggesting that immune cells other than CD4 + T cells might also contribute to protection. Changes in splenic architecture have also been reported in mice following P. yoelii and P. chabaudi infection (28,29), and we cannot rule out the possibility that vaccine-induced immunity occurs with structural changes in the spleen or other tissues. Furthermore, it is known that the liver can play an important role in protection (25,26).…”
Section: Discussionmentioning
confidence: 97%
“…Relative to control parasites, mice were able to resist infection with Py17XL-MIF(ϩ) to a significant degree, as evidenced by a prolonged period of infection and a reduction in the overall mortality rate. During malaria, the spleen is essential for the control of infection and the development of protective immune responses (1,32,59). Our preliminary studies of splenic mRNA levels of TNF-␣, IL-6, IL-12, murine MIF, IL-10, and TGF-␤ showed no differences between Py17XL-MIF(ϩ)-infected and Py17XL-GFPinfected mice.…”
Section: Vol 78 2010 P Yoelii Mif Alters the Course Of Blood-stagementioning
confidence: 95%